2006
DOI: 10.1093/cercor/bhl006
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Anatomical Cortical Underconnectivity in Autism: Evidence from an fMRI Study of an Executive Function Task and Corpus Callosum Morphometry

Abstract: The brain activation of a group of high-functioning autistic participants was measured using functional magnetic resonance imaging during the performance of a Tower of London task, in comparison with a control group matched with respect to intelligent quotient, age, and gender. The 2 groups generally activated the same cortical areas to similar degrees. However, there were 3 indications of underconnectivity in the group with autism. First, the degree of synchronization (i.e., the functional connectivity or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

87
751
7
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 926 publications
(857 citation statements)
references
References 52 publications
87
751
7
12
Order By: Relevance
“…The elementary sensory-higher cortical sensory dichotomy is also consistent with the pattern of dichotomous deficits reported in the motor, memory, language, and abstraction domains in studies of the profile of neuropsychologic functioning in high functioning individuals with autism (Minshew, Goldstein, & Siegel, 1997;Williams, Goldstein & Minshew, 2006) and of the impairments in integration of information causing postural instability (Minshew, Sung, Jones, & Furman, 2004). Functional imaging studies using social, language, and reasoning tasks have provided evidence of a generalized pattern of underdevelopment of the higher-order circuitry necessary for these tasks Just et al, 2004;Just et al, 2007;Kana et al, 2006Kana et al, , 2007Koshino et al, 2007;Minshew, Sweeney, & Luna, 2002). The presence of the same pattern of elementary ability-higher ability dissociation in the sensory and motor domains as in the memory, language and abstraction domains suggests that the sensory and motor impairments are involved by the same neurobiological process as the triad of signs and symptoms on which the diagnosis is based.…”
Section: Discussionsupporting
confidence: 66%
“…The elementary sensory-higher cortical sensory dichotomy is also consistent with the pattern of dichotomous deficits reported in the motor, memory, language, and abstraction domains in studies of the profile of neuropsychologic functioning in high functioning individuals with autism (Minshew, Goldstein, & Siegel, 1997;Williams, Goldstein & Minshew, 2006) and of the impairments in integration of information causing postural instability (Minshew, Sung, Jones, & Furman, 2004). Functional imaging studies using social, language, and reasoning tasks have provided evidence of a generalized pattern of underdevelopment of the higher-order circuitry necessary for these tasks Just et al, 2004;Just et al, 2007;Kana et al, 2006Kana et al, , 2007Koshino et al, 2007;Minshew, Sweeney, & Luna, 2002). The presence of the same pattern of elementary ability-higher ability dissociation in the sensory and motor domains as in the memory, language and abstraction domains suggests that the sensory and motor impairments are involved by the same neurobiological process as the triad of signs and symptoms on which the diagnosis is based.…”
Section: Discussionsupporting
confidence: 66%
“…To summarize briefly: it has been hypothesized that interhemispheric connections of the corpus callosum provide inhibition between functionally homologous areas in the left and right hemisphere (Gazzaniga, 2000). Differences in corpus callosum anatomy such as reduced volume or reduced microstructural integrity are related to lower lateralization of function in typical participants and patient groups (Hinkley et al., 2016; Just, Cherkassky, Keller, Kana, & Minshew, 2007; Persson et al., 2006). In turn, lower lateralization is associated with lower performance on cognitive tasks, including executive function tasks (Hinkley et al., 2012; Just et al., 2007; Nagel, Herting, Maxwell, Bruno, & Fair, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in corpus callosum anatomy such as reduced volume or reduced microstructural integrity are related to lower lateralization of function in typical participants and patient groups (Hinkley et al., 2016; Just, Cherkassky, Keller, Kana, & Minshew, 2007; Persson et al., 2006). In turn, lower lateralization is associated with lower performance on cognitive tasks, including executive function tasks (Hinkley et al., 2012; Just et al., 2007; Nagel, Herting, Maxwell, Bruno, & Fair, 2013). Similarly, posterior temporal white matter may provide connections for integration between specialized regions of temporal lobe for verbal and visuospatial working memory with the posterior parietal executive attention network.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction arises because functional underconnectivity between the frontal lobe and other regions has been found in autism in language comprehension (Just et al, 2004;Kana et al, 2006) and Theory of Mind (Castelli et al, 2002) tasks. In addition, the functional connectivity between the frontal and parietal has repeatedly been found to be abnormally low Just, Cherkassky, Keller, Kana, & Minshew, 2007). This particular interregional underconnectivity is relevant here because the Theory of Mind network includes frontal and parietal areas.…”
mentioning
confidence: 81%
“…It is important to consider the structural properties of the brain when describing the functional connectivity and to relate the structural properties to the functional properties revealed by brain activation measures. Previous research has found a correlation between the size of regions of the corpus callosum and the functional connectivity between the cortical regions connected through these regions (Just et al, 2007;Kana et al, 2006). To examine this structure-function correlation in discourse processing, the size of the various segments of the corpus callosum of each participant in the current discourse processing study was measured.…”
mentioning
confidence: 99%